Developing English communication skills for college learners - Lazo, Jennifer T.; Mercado, Maria Cristina P. ; Balcoba, Alexander C. (Mandaluyong City, 2012)
This book 'Developing English Communication Skills for College Learners' (a Worktext for College Learners) is written to prepare and equip students in the tertiary level with basic yet most important English lessons as far as improving communication skills and basic grammar are concerned....The book covers reading selections that comprise of vocabulary enhancers and comprehension activities to provoke students' critical and higher dimensions of thinking skills
Keywords: Communication- Problems, Exercises, etc; English Language- Textbook